A review and reassessment of diffraction, scattering, and shadows in electrodynamics. (May 2018) - Berg, Matthew J.; Sorensen, Christopher M.
A bstract: The concepts of diffraction and scattering are well known and considered fundamental in optics and other wave phenomena. For any type of wave, one way to define diffraction is the spreading of waves, i.e., no change in the average propagation direction, while scattering is the deflection of waves with a clear change of propagation direction. However, the terms "diffraction" and "scattering" are often used interchangeably, and hence, a clear distinction between the two is difficult to find. This review considers electromagnetic waves and retains the simple definition that diffraction is the spreading of waves but demonstrates that all diffraction patterns are the result of scattering. It is shown that for electromagnetic waves, the "diffracted" wave from an object is the Ewald–Oseen extinction wave in the far-field zone. The intensity distribution of this wave yields what is commonly called the diffraction pattern. Moreover, this is the same Ewald–Oseen wave that cancels the incident wave inside the object and thereafter continues to do so immediately behind the object to create a shadow. If the object is much wider than the beam but has a hole, e.g., a screen with an aperture, the Ewald–Oseen extinction wave creates the shadow behind the screen and the incident light that passes through the aperture creates the diffraction pattern. This point of view also illustrates Babinet's principle. Thus, it is the Ewald–Oseen extinction theorem that binds together diffraction, scattering, and shadows.